IMPLEMENTASI REKAYASA LALU LINTAS OLEH SATLANTAS DI JALAN OTISTA DALAM MENGURANGI KEMACETAN LALU LINTAS - Handiyani, Kris Novi (Advances in Police Science Research Journal, 2020)
ABSTRACT This research has a purpose to describe the situation of traffic flow and traffic congestion conditions, describe the kind of traffic engineering implementation and analyze the supporting and inhibiting factors of the form of traffic engineering implementation on Jalan Otista in the Bogor City area to reducing traffic jam. The concepts used in this research are the concept of traffic congestion and the concept of traffic engineering. The theory used is the theory of public policy implementation and management theory. The research approach is using qualitative approach with the type of field research. The location of the research was conducted in the jurisdiction of the Bogor City resort police which focused on Jalan Otista (Otto Iskandardinata). Data collection techniques consist of observation, interview and document study. Data analysis techniques consist of data reduction, data present and making conclusion and verification. The results showed that the congestion on Jalan Otista before the implementation of the SSA reached the level of LoS service "D". After the implementation of the alternative SSA I (counter clockwise direction) is at LoS "C", but the other road experiences LoS to "E". Therefore carried out the application of alternative SSA II (clockwise). Jalan Otista underwent an "E" LoS, so that the police carried out limited engineering by opened and closed system to the road on Jalan Pajajaran towards Jalan Otista switch to Jalan Baranangsiang. The supporting factors for the implementation of traffic engineering are adequate facilities and infrastructure, the enthusiasm and commitment of members of the Bogor City Traffic Police and a positive response from the people. While the inhibiting factors are the behavior and complaints of the people, the quantity of human resources from the Bogor Kota Traffic Unit and related agencies, and the lack of synergy between the municipal government with the police and other agencies. Keywords: Traffic engineering, LoS Service Level, Implementation